177k views
0 votes
-6m2 - 7m + 8) - (2m2 - 5m - 9

2 Answers

1 vote


(-6m^2-7m+8)-(2m^2-5m-9)\\\\=-6m^2-7m+8-2m^2-(-5m)-(-9)\\\\=-6m^2-7m+8-2m^2+5m+9\qquad\text{combine like terms}\\\\=(-6m^2-2m^2)+(-7m+5m)+(8+9)\\\\=\boxed{-8m^2-2m+17}

User Ryankuck
by
7.4k points
3 votes

Answer:

-8m^2 -2m +17

Explanation:

(-6m^2 - 7m + 8) - (2m^2 - 5m - 9)

Distribute the minus sign

(-6m^2 - 7m + 8) - 2m^2 + 5m + 9

I like to line them up vertically

-6m^2 - 7m + 8

- 2m^2 + 5m + 9

---------------------------

-8m^2 -2m +17

User Virgiliogm
by
7.6k points